Simulation Analysis of Soil Covering Process. (July 2020) - Li, Liyan; Gong, Xin; Xu, Ting; Guo, Pan
Abstract: Soil mulching device is an important part of precision seeder, its structural parameters and performance will directly affect the uniformity of seed distribution and the thickness of soil, and ultimately affect crop yield. Using the EDEM tool based on the discrete element method, the optimized structure of the earth covering device was simulated and analyzed. The soil-slot test was used as a comparative test of the soil simulation experiment. The comparison between the results of the simulation test and the earth covering process test confirmed the applicability of the discrete element method to the earth covering process, which provides a new way for the research and design of the earth covering device and the earth covering process.